Basal or stimulated thyroglobulin in evaluating response to treatment in papillary thyroid carcinoma? A retrospective cohort study - Barreto, Leticia [UNESP]; Ferreira, Deborah Cristina Goulart [UNESP]; Corrente, José Eduardo [UNESP]; Soares, Carlos Segundo Paiva [UNESP]; Oliveira, Cristiano Claudino; Terra, Simone Antunes [UNESP]; Moriguchi, Sonia Marta [UNESP]; Koga, Katia Hiromoto [UNESP]; Tagliarini, José Vicente [UNESP]; da Silva Mazeto, Gláucia Maria Ferreira [UNESP] (Springer Nature, 2024)
Objective: It is not clear whether response to initial treatment in papillary thyroid carcinoma (PTC) patients is best evaluated by measuring thyroglobulin (Tg) in the presence of levothyroxine (BTg) or when stimulated by elevated TSH (STg). The aim of this study was to evaluate whether response to therapy 1 year after initial treatment changes with the use of STg in relation to BTg in PTC patients treated with total thyroidectomy (TT) and radioiodine (131I), and, if observed, to assess which response is better associated with clinical course. Subjects and methods: This is a retrospective study of 148 PTC patients submitted to TT and 131I. We analyzed the response to therapy (excellent, biochemical incomplete, or indeterminate) at 1 year after initial treatment, using BTg or STg, and compared which method was better associated with “excellent response at final evaluation.” Results: Twenty-eight patients (20.4%) presented change in response to therapy, with 17 of these (60.7%) presenting a worse response. Response using STg was 1.6 times better associated with proposed outcome [odds ratio (OR) = 4.61; confidence interval 95% (IC95%): 2.13–9.98] than with BTg (OR = 2.84; IC95%: 1.33–6.06). Conclusion: Response to therapy at 1 year using STg was altered in approximately 20% of cases and therefore proved to be a better predictor of excellent response in the last evaluation.
Keywords: Biomarkers, Tumor; Clinical evolution; Prognosis; Thyroglobulin; Thyroid cancer, Papillary